2015
DOI: 10.1007/s13361-015-1282-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening Method for the Discovery of Potential Bioactive Cysteine-Containing Peptides Using 3D Mass Mapping

Abstract: Animal venoms and toxins are a valuable source of bioactive peptides with pharmacologic relevance as potential drug leads. A large subset of biologically active peptides discovered up till now contain disulfide bridges that enhance stability and activity. To discover new members of this class of peptides, we developed a workflow screening specifically for those peptides that contain inter- and intra-molecular disulfide bonds by means of three-dimensional (3D) mass mapping. Two intrinsic properties of the sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…org/help/Toxins. We cannot but conclude that our previous observation [18] still stands, with 6.66% of all residues being Cys in Tox-prot, whereas only 1.39% of all residues are Cys in UniProt.…”
Section: Metaspace-generated Mshc Image (Left) Obtained Of Biobanked ...contrasting
confidence: 75%
See 4 more Smart Citations
“…org/help/Toxins. We cannot but conclude that our previous observation [18] still stands, with 6.66% of all residues being Cys in Tox-prot, whereas only 1.39% of all residues are Cys in UniProt.…”
Section: Metaspace-generated Mshc Image (Left) Obtained Of Biobanked ...contrasting
confidence: 75%
“…As stated in our previous publication [18], many biologically active secretory peptides contain one or multiple disulfide bridges, in part due to/their contribution to the peptides' stability and activity. We concluded that the presence of Cys can 2d shows a theoretic isotope envelope of oxytocin with its cystine disulfide bridge formed.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations